A Cross-sectional to determine how Knowledgeable pregnant Women attending Antenatal Care at Lira Regional Referral Hospital are regarding the benefits and contraindications of Physical Activity during Pregnancy. - Felex Okori (Student's Journal of Health Research Africa, 2022)
Background.